On the Development of the Hellenic Digital Library of Arabic Historical Sources: A Framework for Digital Scholarship in the Humanities - Efstathios Lianos-Liantis; Emmanuil Karageorgoudis; Marco Miotto; Papakostas, Christos (Heritage, 2025)
Despite Greece’s historical and geographical significance in the Mediterranean, there is currently no national digital repository offering systematic access to Arabic chronicles, diplomatic letters, and travelogues from the eighth to sixteenth centuries. This absence critically impedes rigorous Arabological and Islamological research within Greek academia and restricts the educational landscape to predominantly Eurocentric perspectives. The Hellenic Digital Library of Arabic Historical Sources (HDB-AHS) is proposed as a pre-implementation targeted solution, presenting a trilingual (Greek–English–Arabic) digital platform designed to aggregate, preserve, and openly disseminate these vital sources. The article outlines a six-phase implementation plan combining IIIF, TEI-XML, FAIR for interoperability and reuse and CARE principles where community authority or sensitivity requires it, and open licensing with a robust rights–clearance framework for modern copyrights and sensitive materials. Beyond academic benefits, the project aspires to act as a meeting point of cultures, offering concrete tools for building bridges, combating intolerance, and fostering intercultural understanding. In a world that is rapidly changing, the creation of such an inclusive and responsibly curated digital resource is vital not only for advancing research but also for supporting dialogue and mutual respect across societies. The HDB-AHS provides a blueprint for similar initiatives in underrepresented fields.